Sprouting facilitates the antiglycative effect of black soybean (Glycine max (L.) Merr.) by promoting the accumulation of isoflavones - Qian Zhou; Yuxuan Chen; Lifang Peng; Jun Wu; Wen Hao; Mingfu Wang (Current Research in Food Science)
The exposure of advanced glycation end products (AGEs) can induce chronic inflammation, oxidative stress, and accelerated aging, contributing the onset and progression of many diseases especially diabetic complications. Therefore, the searching of antiglycative foods is of practical significance, which may serve as a strategy in the attenuation of AGEs-associated diseases. In this study, we evaluated the antiglycative potential of some beans and bean sprouts that were common in our daily life. The results revealed that sprouting enhanced the antiglycative activity of beans, with black soybean sprouts demonstrating the highest efficacy (4.92-fold higher than the unsprouted beans). To assess practical implications, we examined the antiglycative activity of black soybean sprouts in pork soup, a popular food model that incorporates sprouts. Our findings confirmed the inhibitory effect on a dose-dependent manner. Through open column fractionation, we identified isoflavones and soyasaponin Bb as the candidates responsible for these effects. Additionally, compare to the unsprouted black soybeans, we found significant increases in the levels of antioxidative properties (2.51-fold), total phenolics (7.28-fold), isoflavones, and soyasaponin Bb during the sprouting process. Further studies determined that genistein, genistin, and daidzin were the major antiglycative compounds in black soybean sprouts. Collectively, this study emphasizes the benefits of sprouted beans and offers foundation for the development of functional sprouting foods.